Hubungan Tingkat Stres Akademik dengan Perilaku Help Seeking pada Mahasiswa Tingkat Akhir - Putri, Nur Grianing (Jurnal Kesehatan Ilmiah Indonesia (Indonesian Health Scientific Journal), 2022)
The help seeking behavior can be caused by academic stress felt by final-year students. Academic stress has a negative impact and can cause anxiety, hopelessness, loss of self-confidence, and even mental disorders. This study aim to know the relationship between academic stress levels with help seeking behavior in final-year students of the Faculty of Nursing. This study used correlative descriptive with a cross sectional approach. Samples were taken with a simple random sampling technique of 81 respondents. The analysis used is bivariate analysis with chi square test. There were 58 people (85,3%) with mild-moderate academic stress level had low-moderate help seeking behavior, while 10 people (14,7%) with mild-moderate academic stress level had high help seeking behavior. Based on statistical test results, p value (0,058) > α (0,05). The result of this study showed that there is no relationship between academic stress level help seeking behavior of final year students of School of Nursing. Respondents with mild-moderate stress tend to have low-moderate help seeking behavior. Expected efforts can be given to maintain stress level within good limits and be able to do adaptive coping.